Picture – Object Recognition in Kea (Nestor notabilis) - Wein, Amelia; Gajdon, Gyula K; Schwing, Raoul; Wright, J (Ethology, 2015)
Although pictures are widely used as stimuli in cognitive experiments with both humans and animals, the question of how subjects interpret pictures receives less attention. Gaining a better understanding of this is especially important when working with avian subjects, as their visual anatomy and processing is different from that of humans, and even differs from one avian species to another. Successful testing for picture recognition in birds has been carried out mainly with pigeons, but no such research has been explicitly performed with ‘brainy’ birds like parrots, despite the fact that these have been the subject of exciting cognitive research. This study tested kea (Nestor notabilis) mountain parrots for picture–object recognition using a procedure which required the transfer of a learned discrimination task between pictures and objects. Kea successfully showed both picture‐to‐object and object‐to‐picture transfer and performed at a comparable level when pictures were displayed on a touch screen or as printed photographs.